Memperkuat Integrasi Nasional di Tengah Keberagaman Indonesia - Septria Sa'duh; Sasmi Nelwati (Universitas Maritim AMNI Semarang, 2024)
Indonesia is an archipelagic country rich in cultural, ethnic, religious, and linguistic diversity. This diversity is both a potential and a challenge in maintaining the unity of the nation. This article aims to analyze efforts to strengthen national integration amidst the diversity of Indonesia. The method used is a literature study by collecting and analyzing reliable sources related to national integration. The analysis shows that national integration in Indonesia can be strengthened through several approaches, namely: 1) Strengthening the Pancasila ideology as the unifying force of the nation; 2) Prioritizing dialogue and cooperation between different community groups; 3) Realizing social and economic justice; 4) Increasing the role of government institutions and civil society; and 5) Strengthening national identity through education and culture. These efforts are expected to strengthen national integration amidst the diversity of Indonesia.